Qualitative analysis of potential adulterants of cheese lipids using Fourier Transform Infrared (FTIR) spectroscopy - Mirghani, Mohamed Elwathig Saeed; Marikkar, Mohammed Nazrim; Alkhalf, Maha Ibrahim (2015)
Food products containing lard are prohibited to be consumed for the followers of Islamic and Orthodox Jewish religions. Samples of four different brands of imported cheeses were purchased from local markets in Malaysia and King Saudi Arabia (KSA). The objective of this study is to detect adulteration of fats in cheese, especially when using lard to replace milk fats. That is because lard is a non halal for Muslims as well as non-Kosher for Jews. Lipids were extracted from cheese samples by using liquid-liquid extraction using a mix of chloroform and methanol (2:1, v/v) as solvent. Then alcohol phase was removed, and the chloroform phase containing lipids was evaporated under vacuum using a rotary evaporator. Extracted lipids were dried by mixing with anhydrous Na2SO4, filtered and kept at 4⁰C until analysis. Lard sample was extracted by rendering adipose tissues of pig at 80-100⁰C for about 2 hours. The rendered lard was decanted and filtered through Whatman No. 1 filter paper and anhydrous Na2SO4 was added to the extract to remove residual moisture. The collected cheese fat samples and lard were then cooled down to room temperature and analyzed using Fourier transform infrared (FTIR) spectrophotometer. Spectra were collected by co-adding 16 scans from 4000 to 550 cm-1 wavelengths at 1 cm-1 resolution and a strong apodization was used. After each measurement, the crystal of Attenuated total reflectance element (ATR) element was cleaned three times with acetone and dried. The cleaned crystal was checked spectrally to ensure that no residue remained from the previous sample. The result showed that FTIR spectroscopy could be used to differentiate qualitatively between lard and other types of fats (extracted from cheese samples) in the regions at 3007, 1096–1115, 756 and 720 cm–1 showing different absorbance’s representing unsaturation -C=C-, =C-H stretch/-C–O–C, -C-H out of plane bending and cis/trans isomers, respectively. As a result of this research, it could be concluded that FTIR spectroscopy is a rapid, steadfast technique for the detection of non-halal lipids in cheese.